Implementasi Technological Pedagogical Content Knowledge (TPACK) terhadap Keterampilan Mengajar di Sekolah Dasar - Diaz Putri Amelia; Monica Oktafianti; Pingkan Regi Genika; Raisa Ayu Luthfia (Departement of Mathematics Education, 2023)
The scope of technology today is very broad, including the world of education. In the world of education, there is an integration of technology that is applied to the learning process. In particular, elementary school teachers who must have teaching skills. One of them is Technological Pedagogical Content Knowledge (TPACK). This study aims to find out about the teaching skills of teachers in elementary schools by applying Technological Pedagogical Content Knowledge (TPACK) to improve student learning outcomes. The integration of TPACK can change the class atmosphere to be fun, such as showing pictures, videos, and material that is poured on PowerPoint. The results showed that there was an increase in student learning outcomes in each subject by applying TPACK. However, it is not effectively used during distance learning due to several constraints, such as inadequate internet network, mobile phone memory that fills up quickly, and quotas run out quickly. In addition, there are several teachers who are less proficient in technology so that in implementing TPACK in learning it is not optimal.